2007
DOI: 10.1245/s10434-007-9574-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Graded Histologic Response After Neoadjuvant Chemotherapy Predict Survival for Completely Resected Gastric Cancer?

Abstract: Posttreatment nodal status and perineural or vascular invasion at resection, but not graded histologic response, independently predict DSS after neoadjuvant chemotherapy and surgical resection of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
4
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 10 publications
10
89
4
5
Order By: Relevance
“…Whether pathological response is an indicator of efficacy for neoadjuvant treatment for GC is controversial [35][36][37]. In this study, pathological response did not correlate with survival, but grade 0 (no evidence of tumor regression) was associated with extremely poor survival.…”
Section: Discussionmentioning
confidence: 58%
“…Whether pathological response is an indicator of efficacy for neoadjuvant treatment for GC is controversial [35][36][37]. In this study, pathological response did not correlate with survival, but grade 0 (no evidence of tumor regression) was associated with extremely poor survival.…”
Section: Discussionmentioning
confidence: 58%
“…Since 1999, response to neoadjuvant chemotherapy has been well established to be predictive of survival in patients with resectable gastric cancer 26,27 . Another more recent study conducted at Memorial Sloan-Kettering Cancer Center showed that 3-year disease-specific survival was significantly higher for patients achieving a better than 50% pathologic response to preoperative chemotherapy than for those achieving a lesser histologic response (69% vs. 44%) 28 . Currently, identifying the patients who would best respond to neoadjuvant therapy remains a challenge; no demographic variable or tumour characteristic can, as yet, identify responders a priori.…”
Section: Discussionmentioning
confidence: 97%
“…However, the therapeutic strategies by which clinicians distinguish between the various treatment options remain a contentious issue. One point of clinical importance is that, although preoperative therapy has the potential to improve the therapeutic outcome for responders (42), it runs the risk of shifting the status of nonresponders from potentially resectable to unresectable, despite that radical resection is the only curative treatment modality, requiring the predictive marker for treatment response. Therefore, information on Reprimo promoter methylation may provide much needed guidance in determining the therapeutic strategies, such as the selection of the most suitable patients for preoperative therapy in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%